Predictive Ability of Social Interest and Defense Mechanisms upon Psychological Exhaustion Syndrome Among Mental Health Professionals: - Al-nemrat, Hind Ahmad; Al-shraifin , Ahmad Abdullah (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to determine the predictive ability of social attention and defense mechanisms in relation to mental exhaustion syndrome among mental health workers. The study sample consisted of 399 mental health workers. Methods: The study employed a predictive descriptive approach. To achieve the objectives, three scales were used to measure psychological exhaustion syndrome, social attention, and defense mechanisms. Results: The results indicated that the overall level of psychological exhaustion was low, while the level of social attention was very high. Among the sample members, neurotic mechanisms were the most prevalent, followed by mature mechanisms, with immature mechanisms being the least prevalent. The results also revealed a predictive ability of social interest and defense mechanisms in relation to psychological burnout syndrome. Specifically, mature mechanisms explained 11.7% of the total variance in fatigue, followed by social concern, which contributed 7.1% of the total variance. Conclusion: Further studies are necessary, involving a broader range of variables and mental health workers, to address the emotions that workers may encounter in their work. Additionally, it is important to enhance the role of supervisory programs, monitor the professional and psychological needs of mental health workers, and conduct regular medical examinations. This will facilitate the identification and treatment of symptoms resulting from dealing with cases that may deplete their energies and resources.